Association between Dietary Acid Load and Depression, Anxiety, and Stress: A Systematic Review - Mohammad Javad Zare; Samaneh Madani; Afsane Ahmadi (International Journal of Nutrition Sciences, 2025)
Background: Several studies have suggested a potential association between diet and mental disorders. This systematical review investigated the association between dietary acid load (DAL) and mental health outcomes such as depression, anxiety, and stress.Methods: Online databases including PubMed, Scopus, and Web of Science searched for published studies using relevant keywords until January 2024.Results: Seven studies were included in this systematic review, of which 6 were on adults. Five out of six studies on depression evaluated dietary acid load (DAL) with potential renal acid load (PRAL) method of which 3 of them reported a significant association. Three out of five studies that used net endogenous acid production (NEAP) method also presented a significant direct association. Furthermore, five studies examined the relationship between DAL and anxiety and all revealed a significant direct association. Moreover, a direct association between DAL and stress was noticed in two other studies. In terms of children and adolescents, a prospective study found no association between DAL and overall mental health among children and adolescents.Conclusion: Dietary acid load, especially PRAL, may be associated with psychological disorders like depression, anxiety, and stress among women. However, in the interpretation of these findings, it should be considered that the heterogeneity among studies is high as most of them conducted the study on women and participants had underlying diseases; so the conclusion cannot be extended to the overall population due to the limited number and design of current studies.